Pattern Based Security Testing - Paulo Jorge Moreira de Araújo (2017)
Today, a software application to have quality must work flawlessly and be safe. However, exposure of applications to undesirable attacks is common and brings new challenges. Developers are concerned mainly to create applications that work properly and sometimes they neglect the security of the application and that is why test the developed application is critical to ensure that we are delivering a quality and reliable product.One way to increase the quality of application is by testing. However, the test implementation requires time and money which are limited resources. In order to combat this problem have emerged in recent years a number of testing tools based on different methodologies that try to make faster and more systematic testing process. One of these methodologies is testing based on models/patterns which have been increasingly accepted.The PBGT (Pattern Based GUI Testing) project allowed the development of pattern based testing tools to test applications through graphical user interface (GUI).This research work aims to extend the tools developed in PBGT project for testing the security aspects. It will be necessary draw up an inventory of typical security issues and security patterns for which then will be developed generic technical test to evaluate security aspects in different web applications.